(untitled) (Global Journal of Human-Social Science, 2025)
This paper analyzes how the digital renminbi (e-CNY) may impact the structural power of the U.S. dollar and discusses its primary limitations. We adopt the framework of the dollar’s structural power within US hegemony, highlighting the political consequences of its central role. Next, we examine China’s digitalization from two perspectives: monetary and operational, and within the context of the Digital Silk Road, whose four pillars -infrastructure, technology, ecommerce, and governance -support the e-CNY’s dissemination. This paper argues that the e-CNY’s launch might provide a new impetus for the renminbi’s internationalization, particularly in regional payments and e-commerce. However, this does not challenge the dollar’s structural dominance in the short term, as the limits to the expansion of the e-CNY in the international monetary hierarchy remain quite significant.